Capacity Degradation and Aging Mechanisms Evolution of Lithium-Ion Batteries under Different Operation Conditions - Luo, Guoqing; Zhang, Yongzhi; Tang, Aihua (Energies (Basel), 2023)
Since lithium-ion batteries are rarely utilized in their full state-of-charge (SOC) range (0–100%); therefore, in practice, understanding the performance degradation with different SOC swing ranges is critical for optimizing battery usage. We modeled battery aging under different depths of discharge (DODs), SOC swing ranges and temperatures by coupling four aging mechanisms, including the solid–electrolyte interface (SEI) layer growth, lithium (li) plating, particle cracking, and loss of active material (LAM) with a P2D model. Additionally, the mechanisms causing accelerated capacity to drop near a battery’s end of life (EOL) were investigated systematically. The results indicated that when the battery operated with a high SOC range, the capacity was more prone to accelerated degradation near the EOL. Among the four degradation mechanisms, li plating was mainly sensitive to the operation temperature and SOC swing ranges, while the SEI growth was mainly sensitive to temperature. Furthermore, there was an inhibitory interaction between li plating and SEI growth, as well as positive feedback between LAM and particle cracking during battery aging. Additionally, we discovered that the extremely low local porosity around the anode separator could cause the ‘knee point’ of capacity degradation.